(untitled) (Third Sector Social Economic Review, 2018)
Cooperatives deserve to be accepted as a third sector besides the public and private sectors, in terms of the benefits they provide to their partners and society. There are people in the center of the cooperatives. Cooperatives striving for economic and social development of their partners thus contributing to the economic and social development of the society. Cooperatives face opposition in almost every region of the world. The contributions of these cooperatives to economic and social life are important in the scale of countries. Cooperatives are founded on a variety of activity in Turkey. The size of the Cooperative and the number of partners demonstrates the importance of the cooperative sector in Turkey. However, Turkish co-operatives are inadequate in calculating the contribution of cooperatives to the country’s economy. This is because the quantitative data on cooperatives is limited, that is, the economic indicators are low. Cooperatives are outnumbered in Turkey but these cooperatives are not successful. According to the results of the survey on Turkish cooperative legislation, the legislation of cooperatives needs to be restructured. There should be a separate ministry responsible for cooperatives and a single legal foundation in Turkey.